Novel synthesis of Silicon/Carbon nanotubes microspheres as anode additives through chemical vapor deposition in fluidized bed reactors. (February 2021) - ZHAO, Hong; TU, Ning; ZHANG, Weibin; ZHANG, Min; WANG, Jian
Abstract: Herein, we synthesized Si/carbon nanotube microspheres (Si/CNTsS) via a two-step process, where the carbon nanotube microspheres (CNTsS) were first fabricated by spray drying, followed by the deposition of nano-silicon on/into the obtained CNTsS through chemical vapor deposition (CVD) in fluidized bed reactors (FBR). By adding the Si/CNTsS materials as an anode additive with the mass ratio of 10% to graphite, the hybrid anode possess a high specific capacity of over 500 mAh/g, much higher than that of commercial graphite (350mAhg −1 ). Most strikingly, the preparation cost of nano–Si can be reduced effectively via the CVD in FBR method, thus the responding Si/CNTsS have the potential to be widely used as practical anode additive in high-energy-density lithium-ion batteries. Graphical abstract: Abstract : We synthesized Si/carbon nanotube microspheres (Si/CNTsS) via spry drying followed by CVD in fluidized bed reactors (FBR). Image, graphical abstract